Społeczna odpowiedzialność w relacjach międzysektorowych - Szymankiewicz, Maria Janina (Annales. Etyka w Życiu Gospodarczym, 2015)
The performance and development of an organisation depends not only on the organisation itself, but – to an increasing extent – on its relationships with its surroundings. This also refers to cross-sector relationships outside the world of business. Thus, the purpose of the article is to analyse the cross-sector collaboration between public administration and non-governmental organisations (NGOs), and to highlight its fundamental terms and conditions, e.g. trust and social responsibility. The more honesty there is in such relations, the more trust and willingness to co-operate there arises in both parties. The analysed model of collaboration between public administration and NGOs seems to be a helpful tool for the development of collaboration based on social responsibility.